MHC Bias by T Cell Receptors: Genetic Evidence for MHC and TCR Co-Evolution - Baker, Brian M. (Trends Immunol, 2016)
MHC restriction is a fundamental tenet of T cell biology, but the underlying mechanisms have remained controversial. The extent to which T cell receptors are biased towards MHC proteins in particular has been widely discussed. In a recent paper, Sharon et al. report direct evidence for co-evolution between TCR and MHC genes, helping explain how MHC compatibility and bias can be encoded within T cell receptors.